The Writers’ Workshop Impact to the Writing of English Foreign Language (EFL) Learner in Indonesia - Masrul, Masrul; Rasyidah, Ummi (Tamaddun Life, 2023)
The research delved into assessing the impact of the Writers' Workshop approach on the English writing proficiency of students exhibiting diverse writing abilities. The Writers' Workshop is an instructional method that prioritizes cultivating students' writing skills through a sequence of imaginative and reflective activities. Within this approach, students are empowered to become active writers, granted the freedom to explore their ideas, craft their own manuscripts, and engage in collaborative efforts with their peers. In Riau, Indonesia, thirty-five students (19 females and 16 males) participated in English writing instruction grounded in the Writers' Workshop framework. This intervention occurred once a week for a continuous sixteen-week period. As part of the evaluation, students were tasked with composing an opinion essay as both a pre-test and post-test to gauge their writing proficiency. Notably, there was a significant improvement in the writing results across all groups, each displaying distinctive outcomes. The advanced group exhibited more pronounced benefits compared to the intermediate and novice groups, evident in the content of their essays. This disparity underscores the effectiveness of the Writers' Workshop approach, particularly in catering to varying skill levels. The positive strides observed in the students' writing abilities signify the potential of this method to foster holistic development in English writing skills, emphasizing the importance of tailored approaches in heterogeneous learning environments.